Investigating the effect of green hybrid fibre on toughening and mechanical properties of iron-tailing sand concrete - Huawang Shi; Zhenyao Shi; Bo Zhang; Huilin Chen (Građevinar)
To improve the brittleness and susceptibility to cracking of iron tailings sand concrete, fibre blending was employed to toughen and resist cracking in the material. In this study, two inexpensive and environmentally friendly fibre materials were used: recycled tire steel fibre (RTSF) and coconut fibre (CF). The two fibre materials were blended and the resulting mixture was subjected to a series of performance tests, including compressive, tensile, flexural, impact, and bending tests. The effects of the fibre doping method and amount on the toughness and mechanical properties of iron tailings sand concrete were investigated in terms of the law of effect of the blended fibre admixture on the toughness and mechanical properties of iron tailings sand concrete. The results show that adding two types of fibres can effectively improve the toughness and mechanical properties of the specimen, and the hybrid fibre has a more obvious effect. Compared with the blank control group (Non), the compressive strength, splitting tensile strength, bending strength, impact strength, and bending peak load of the concrete with 0.75 % RTSF and 0.2 % CF increased by 20.8 %, 42.9 %, 40.4 %, 92.4 %, and 37.5 %, respectively. Combined with the theory and fracture surface morphology analysis, it was shown that recycled tire steel fibres play a major role in cracking resistance, while coconut fibres play a toughening role.